An in-depth review on phytochemistry and pharmacological significance of phyllanthus emblica linn. - Anjali Gupta; Vikram Sharma; Bibhu Prasad Moharana; Anil Kumar; Tanmay Ghosh; Ananya Bhowmick; Sivamani S; Viabhav Kumar Upadhayay; Sanmati Kumar Jain (Revista Electronica de Veterinaria, 2024)
Background: Phyllanthus emblica, commonly known as Amla or Indian gooseberry, has been recognized for its extensive medicinal properties and is a staple in traditional medicine systems such as Ayurveda and Traditional Chinese Medicine. This review aims to comprehensively explore its phytochemical composition and pharmacological significance.Objective: The objective of this review is to summarize the current understanding of the phytochemistry and pharmacology of Phyllanthus emblica, highlighting its potential therapeutic applications and safety profile.Methods: A systematic review of literature was conducted, focusing on peer-reviewed articles, clinical studies, and relevant pharmacological research on Phyllanthus emblica. Information was categorized into sections, including botanical description, phytochemical composition, pharmacological activities, mechanisms of action, clinical studies, toxicological profile, and future perspectives.Key Findings: The findings indicate that Phyllanthus emblica is rich in bioactive compounds, including tannins, flavonoids, phenolics, and vitamins. Its pharmacological activities encompass potent antioxidant, anti-inflammatory, anticancer, antimicrobial, hepatoprotective, cardioprotective, gastroprotective, and antidiabetic effects. Toxicological studies demonstrate a favorable safety profile, with minimal adverse effects reported at recommended dosages.Conclusion: Phyllanthus emblica holds significant promise as a therapeutic agent due to its extensive health benefits and safety. Further research is needed to address challenges in standardization and formulation to facilitate the development of P. emblica-based pharmaceuticals and nutraceuticals. Integrating traditional knowledge with modern scientific validation will enhance its role in contemporary health practices, paving the way for innovative health solutions.